Memaksimalkan KreatiVfitas melalui Metode PBL dengan Media Canva pada Murid Fase D kelas VII SMPN 7 KMB Kubu Raya - Yosef Ronni; Demitria Selvita Alvianey (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
Low learning outcomes in Catholic Religious Education for grade VII students at SMP Negeri 7 Kuala Mandor B are caused by conventional teaching methods and monotonous learning media. This study aims to enhance student creativity through the Problem-Based Learning (PBL) method by utilizing Canva as an interactive digital medium and developing problem-identification skills. The research involved 30 grade VII students in September 2025, using a two-cycle approach: planning, action, observation, and reflection. Data were collected through observation sheets, written tests, and reflection sheets. Indicators of success included at least 80% student participation in discussions, an average learning outcome score of 75 or higher, and improved reflective thinking. The first cycle showed increased creativity, though reflection was limited. After refining the reflection guide and methods in the second cycle, there was a notable improvement in reflection quality, discussion participation exceeded 80%, and average cognitive scores surpassed 75. Canva effectively enhanced creativity and understanding of Catholic Religious Education materials. In conclusion, combining Canva digital media with PBL significantly improves learning outcomes and reflective thinking skills of grade VII students.